Evaluation protocol of fish farming good management practices in the state of Pará: case study (Research, Society and Development, 2020)
This paper aimed to propose a protocol for good management practices (GMP) evaluation in fish farming. For such purpose, an initial protocol was created through bibliographic survey, field observations and interviews with fish farmers about management of 32 commercial fish farms in the state of Pará, to determine the susceptible points to interventions to low complexity and low-cost. Subsequently, 21 procedures were defined to compose the protocol with following steps: transport, settlement, biometrics, food management, water quality and harvest. For use, each project must have its procedures scored at 0 (zero), when it does not meet the established standard, or 1 (one), when it does. The sum of averages responses in each stage indicates the project adequacy degree in: little adequate (0 to 2), potentially adequate (2.1 to 4) or adequate (4.1 to 6). The suggested protocol is expected to assist fish farmers in adopting good management practices, contributing to improve their project adequacy.